"TO TRANSLATE WITHOUT BETRAYING": THE HOUSE OF BERNARDA ALBA IN AN UNPUBLISHED TRANSLATION INTO BRAZILIAN PORTUGUESE: THE HOUSE OF BERNARDA ALBA IN AN UNPUBLISHED TRANSLATION INTO BRAZILIAN PORTUGUESE - Loureiro Andretta, Bárbara; Ferrari Montemezzo, Luciana (Revista de Letras, 2025)
This text aims to analyze some solutions found during the translation process of La casa de Bernarda Alba (1936) into Brazilian Portuguese. A play that Clarice Lispector and Tati de Moraes dedicated themselves to translate. It will be given special attention to the translation of metaphors proposed by Iñesta Mena and Pamies Bertrán (2002) and Sanz Martín (2015). This translation is still unpublished and is part of Clarice Lispector's legacy, which is found at Casa de Rui Barbosa in Rio de Janeiro, Brazil. The study of the typed document does not provide any clue concerning to whom or what theater company it was written for or if the play was performed. However, this document not only stands out as an interesting object of research, but it is also an important material for the analysis of cultural exchanges between the two countries (Paz, 1983). The result is surprising: the writers were historically and culturally away from each other but Lorca, Clarice and Tati became close through the literature. From this closeness, the last work produced by the Spanish playwright reached the Brazilian public through a play performed by the Quartas Dramáticas group (UnB) in 2017.